Optimization of the precursor supply for an enhanced FK506 production in Streptomyces tsukubaensis - Schulz, Susann; Schall, Christoph; Stehle, Thilo; Breitmeyer, Christian; Krysenko, Sergii; Mitulski, Agnieszka; Wohlleben, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2022)
Tacrolimus (FK506) is a macrolide widely used as immunosuppressant to prevent transplant rejection. Synthetic production of FK506 is not efficient and costly, whereas the biosynthesis of FK506 is complex and the level produced by the wild type strain, Streptomyces tsukubaensis, is very low. We therefore engineered FK506 biosynthesis and the supply of the precursor L-lysine to generate strains with improved FK506 yield. To increase FK506 production, first the intracellular supply of the essential precursor lysine was improved in the native host S. tsukubaensis NRRL 18488 by engineering the lysine biosynthetic pathway. Therefore, a feedback deregulated aspartate kinase AskSt* of S. tsukubaensis was generated by site directed mutagenesis. Whereas overexpression of AskSt* resulted only in a 17% increase in FK506 yield, heterologous overexpression of a feedback deregulated AskCg* from Corynebacterium glutamicum was proven to be more efficient. Combined overexpression of AskCg* and DapASt, showed a strong enhancement of the intracellular lysine pool following increase in the yield by approximately 73% compared to the wild type. Lysine is coverted into the FK506 building block pipecolate by the lysine cyclodeaminase FkbL. Construction of a ∆fkbL mutant led to a complete abolishment of the FK506 production, confirming the indispensability of this enzyme for FK506 production. Chemical complementation of the ∆fkbL mutant by feeding pipecolic acid and genetic complementation with fkbL as well as with other lysine cyclodeaminase genes (pipAf, pipASt, originating from Actinoplanes friuliensis and Streptomyces pristinaespiralis, respectively) completely restored FK506 production. Subsequently, FK506 production was enhanced by heterologous overexpression of PipAf and PipASp in S. tsukubaensis. This resulted in a yield increase by 65% compared to the WT in the presence of PipAf from A. friuliensis. For further rational yield improvement, the crystal structure of PipAf from A. friuliensis was determined at 1.3 Å resolution with the cofactor NADH bound and at 1.4 Å with its substrate lysine. Based on the structure the Ile91 residue was replaced by Val91 in PipAf, which resulted in an overall increase of FK506 production by approx. 100% compared to the WT.